2013
DOI: 10.1371/journal.pone.0074824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Laboratory Standard Washing Using CIPAC Washing Agent and the Domestic Washing on Three Recommended Types of Long-Lasting Insecticidal Mosquito Nets

Abstract: BackgroundOne of the best ways to prevent malaria is the use of insecticide-treated bed nets. Manufacturers pursue easier, safer and more efficient nets. Hence, many studies on the efficacy and wash resistance using World Health Organization standards have been reported. The commonly used detergent is “Savon de Marseille”, because it closely resembles actually used soaps. At the 54th Collaborative International Pesticides Analytical Council (CIPAC) Technical Meeting in 2010, it was suggested to replace it by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Baseline nominal chemical content for Yorkool® was 1.4 g/kg deltamethrin, PermaNet®2.0 was 1.8 g/kg deltamethrin; and Interceptor® was 6.7 g/kg alphacypermethrin. A tolerance limit of ± 25% of the baseline nominal content is recommended in the WHO specifications for unused LLINs [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline nominal chemical content for Yorkool® was 1.4 g/kg deltamethrin, PermaNet®2.0 was 1.8 g/kg deltamethrin; and Interceptor® was 6.7 g/kg alphacypermethrin. A tolerance limit of ± 25% of the baseline nominal content is recommended in the WHO specifications for unused LLINs [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…A negative control from an untreated net was included in each round of cone bioassay testing. If the mortality in the control was > 10%, all the tests for that day were repeated [20].…”
Section: Data Collectionmentioning
confidence: 99%
“…In our experiments, the α-cypermethrin netting and λ-cyhalothrin spray treatments remained in the experimental chicken sheds throughout the day and between experimental replicates were stored outside where they were exposed to UV light, fluctuating heat, humidity and rainwater. Although there is some evidence to suggest that α-cypermethrin degrades under UV light ( WHO, 1989 ) other studies have shown that repeated exposure to UV light did not reduce the efficacy of Interceptor netting ( Ouattara et al., 2013 ). The surface on which the insecticide is applied plays a significant role in determining the effectiveness of the insecticide treatment ( Feliciangeli et al., 2003 ; Mutagahywa et al., 2015 ; Correa et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments the netting and l-cyhalothrin spray treatments remained in the experimental chicken sheds throughout the day and between experimental replicates were stored outside where they were exposed to UV light, uctuating heat, humidity and rainwater. Although there is some evidence to suggest that acypermethrin degrades in UV [47] other studies have shown that repeated exposure to UV did not reduce the e cacy of the Interceptor netting [48]. In addition, the surface on which the insecticide is applied plays a signi cant role in determining the effectiveness of the insecticide treatment [42,49,50].…”
Section: Discussionmentioning
confidence: 99%